2017
DOI: 10.1021/acschemneuro.7b00128
|View full text |Cite
|
Sign up to set email alerts
|

Iminodiacetic Acid-Modified Human Serum Albumin: A Multifunctional Agent against Metal-Associated Amyloid β-Protein Aggregation and Cytotoxicity

Abstract: Metal-induced amyloid β-protein (Aβ) aggregation plays a key role in the pathogenesis of Alzheimer's disease. Although several agents have been recognized to block metal-associated Aβ aggregation, their therapeutic potential is marred due to the high-concentration metal ions in the amyloid plaques. To overcome this problem, we have herein developed iminodiacetic acid-modified human serum albumin (I-HSA) to fight against the aggregation. The multifunctional nature of I-HSA was extensively characterized in inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Elevated levels of Aβ drive its aggregation into soluble oligomer, protofibrils, and finally mature fibrils. , The intermediates of aggregation have been accepted as the most toxic species to neurons. ,, Therefore, Aβ cascade hypothesis strongly supports exploration of inhibitors that can suppress Aβ aggregation and reduce its cytotoxicity for development of potential drug candidates for the treatment of AD. , Meanwhile, investigations have revealed that the homeostasis dysregulation of transition metal ions, especially Cu 2+ , not only mediate Aβ aggregation into high-cytotoxicity species, but also produce reactive oxygen species (ROS) including oxygen-free radicals (HO·) and hydrogen peroxide (H 2 O 2 ) via Fenton-type reactions, which cause severe oxidative stress. ,, Therefore, various metal-ion chelators have been studied for AD treatment. ,, Considering the complexity of AD onset (Aβ aggregation, metal dyshomeostasis, oxidative stress, inflammation, and so on), the concept of “multifunctional inhibitor” has emerged. A multifunctional inhibitor should possess two or more functions, such as inhibition of Aβ aggregation into toxic species and chelation of transition-metal ions to arrest its activities on ROS production as well as on enhancing the amyloid toxicity. , …”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of Aβ drive its aggregation into soluble oligomer, protofibrils, and finally mature fibrils. , The intermediates of aggregation have been accepted as the most toxic species to neurons. ,, Therefore, Aβ cascade hypothesis strongly supports exploration of inhibitors that can suppress Aβ aggregation and reduce its cytotoxicity for development of potential drug candidates for the treatment of AD. , Meanwhile, investigations have revealed that the homeostasis dysregulation of transition metal ions, especially Cu 2+ , not only mediate Aβ aggregation into high-cytotoxicity species, but also produce reactive oxygen species (ROS) including oxygen-free radicals (HO·) and hydrogen peroxide (H 2 O 2 ) via Fenton-type reactions, which cause severe oxidative stress. ,, Therefore, various metal-ion chelators have been studied for AD treatment. ,, Considering the complexity of AD onset (Aβ aggregation, metal dyshomeostasis, oxidative stress, inflammation, and so on), the concept of “multifunctional inhibitor” has emerged. A multifunctional inhibitor should possess two or more functions, such as inhibition of Aβ aggregation into toxic species and chelation of transition-metal ions to arrest its activities on ROS production as well as on enhancing the amyloid toxicity. , …”
Section: Introductionmentioning
confidence: 99%
“…In addition, lactate dehydrogenase (LDH) release assays were conducted to quantitatively assess the cell death, as described previously . In brief, after SH-SY5Y cells were incubated for 24 h, the culture medium was replaced with an FBS-free medium.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, several bifunctional molecules have been designed to inhibit metal ion-associated Aβ aggregation. Conjugating metal chelators onto proteins or nanoparticles is a prevalent method of overcoming the poor biocompatibility and insufficient inhibition effect on metal-Aβ aggregation. , Among the various proteins/nanoparticles, human lysozyme (hLys) is an important natural nonspecific immune protein against bacterial and viral infections . It has been recognized that lysozyme distinctly inhibits the aggregation of Aβ 1‑40 , Aβ 17‑42 , and Aβ 1‑42 , and native hLys was found to colocalize with Aβ plaques in AD patients and could decrease the locomotor dysfunction in a Drosophila model of AD. , Hence, hLys has the potential to fight against AD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 2017a ) developed a Zn 2+ ion specific nano-chelator where iminodiacetic acid conjugated NPs exhibit higher metal scavenging activity associated with potential inhibition of Aβ 42 fibrillation in neuroblastoma cells. Subsequently, another research group further fabricated iminodiacetic acid-modified human serum albumin (I-HSA) conjugated NPs and established multi-faceted activities by effectively scavenging Zn 2+ /Cu 2+ -Aβ 42 aggregates and further remodeling them to amorphous aggregates with reduced neurotoxicity (Xie et al., 2017 ). Zhang et al.…”
Section: Potential Strategies and Ad Nanotherapeuticsmentioning
confidence: 99%